THE RELATIONSHIP OF INCENTIVES FOR EMPLOYEE’S JOB SATISFACTION IN THE EDUCATIONAL INSTITUTIONS: A CASE STUDY AT TIKRIT UNIVERSITY - Omar Subhi Abdullah (Scholar Express Journals, 2022)
The purpose of this study is to determine the reality of the incentive system application for employees at the University of Tikrit in Iraq, as well as their degree of job satisfaction. This study examined whether there is a link between incentives and job satisfaction among the employees of Tikrit University, as well as whether there is a link between the responses of the research sample that are attributed to gender, educational level of the employee and years of experience in the level of their job satisfaction. The researcher then applied the descriptive analytical approach to a sample of (400) personnel at Tikrit University in Iraq, using a questionnaire. The findings revealed that moral incentives are used more frequently than material ones at the University of Tikrit, and employees there have a high degree of job satisfaction. According to the results of the questionnaire, the employees can earn a job compensation that is proportional with their talents and qualifications. It was also discovered that there is a positive relationship between incentives and employee’s welfare, and that there are no statistically significant differences in job satisfaction between men and women at Tikrit University. There are statistically significant differences in the degree of job satisfaction among University of Tikrit employees based on educational level and years of experience
Keywords: Incentives; Job Satisfaction; Educational Leve; Tikrit Universitsy